Analysis of the sport commitment from the perspective of the Self-determination Theory in young football players - F. M. Leo; F. R. Gómez; P. A. Sánchez Miguel; D. Sánchez; T. García Calvo (Asociación Española de Ciencias del Deporte, 2010)
The main aim of this study is to examine the relationships between the three psychological needs and self-determination level regarding sport commitment in young football players. The sample comprised 809 male and female footballers, ranging in age from 11 to 16 years old (M = 13.25; SD = 1.78), that is to say, they belonged to beginners, infantile and cadet categories. The instruments measured psychological needs, self-determined motivation in the sporting practice and sport commitment. The techniques used were descriptive analysis, reliability analysis, bivariate correlations and lineal regression analysis. Results showed a positive association among basics psychological needs and self-determination level with respect to sport commitment. Thus, we suggest that a high self-determination level is related with a greater sport commitment. On the contrary, low self-determinations levels were associated with smaller sport commitment. Finally, we highlight that we should promote sport motives based on enjoyment and satisfaction in young participants to get a longer and higher sport commitment practice. Key Words: motivation, self-determination, commitment, enjoyment, football